Membangun Karakter Melalui Budidaya Pepaya Callina di Desa Silo Kecamatan Silo Kabupaten Jember - Rif’ah Rif’ah (Program Pascasarjana Universitas Ibrahimy, 2018)
Character can be established through formal institutions, non formal or informal. The focus of this study are; 1) Values ​​of characters built through the cultivation of papaya. 2) Implementation of istiqomah character value in cultivation of pepaya. 3) Why are farmers interested cultivation of papaya? Result of this research are; 1) character Values built through the cultivation of pepaya calina that are the values of the character of his relationship with himself, the value of the character of his relationship with the family, the value of the character of his relationship with the community / environment, the character value relating to nationality and the character Allah; 2) Implementation of istiqomah cultivation of calina papaya is: continuous care; 3) Farmers are interested in the cultivation of calina because it has a high selling value.